2018
DOI: 10.1097/md.0000000000012093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphoric acid concentration used for etching on the microtensile bond strength to fluorotic teeth

Abstract: To evaluate the effects of different etching concentrations of phosphoric acid on the microtensile bond strength of Adper Single Bond 2 to fluorotic teeth.Deidentified extracted teeth were collected, including 30 sound teeth, 30 teeth with mild fluorosis, 30 teeth with moderate fluorosis, and 30 teeth with severe fluorosis. The teeth in each group were randomly divided into 3 subgroups (n = 10) that were subjected to acid etching using 35%, 40%, or 45% phosphoric acid. Adper Single Bond 2 (3M, Saint Paul, MN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 14 publications
0
15
0
9
Order By: Relevance
“…[13,15,16] In addition, some scholars have shown that the bond strength of fluorosis tooth was lower than that of healthy tooth, the bond strength increased with the increasing concentration of phosphoric acid, but an excessively high acid concentration can conversely lead to an apparent decline in bond strength. [17] Therefore, in the case of enamel bonding of mild dental fluorosis, the bonding strength of the all acid etching adhesive was higher than that of the selfetching adhesive. The all acid etching bond strength of mild dental fluorosis was higher than the self-etched bond strength.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[13,15,16] In addition, some scholars have shown that the bond strength of fluorosis tooth was lower than that of healthy tooth, the bond strength increased with the increasing concentration of phosphoric acid, but an excessively high acid concentration can conversely lead to an apparent decline in bond strength. [17] Therefore, in the case of enamel bonding of mild dental fluorosis, the bonding strength of the all acid etching adhesive was higher than that of the selfetching adhesive. The all acid etching bond strength of mild dental fluorosis was higher than the self-etched bond strength.…”
Section: Discussionmentioning
confidence: 97%
“…Dental fluorosis (DF) is caused by ingestion of excess fluoride mainly through drinking water. [4,6] At present, regarding the theory of dental enamel bonding, some scholars believed that mechanical chimera, physical adsorption and chemical bonding were the main ways of dental enamel bonding. [7] The retention force between the adhesive and the enamel mainly depended on mechanical fitting, so the surface morphology of the enamel would have a certain effect on the bonding strength.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism is not clear, we speculate that the absence of collagen in enamel [35] makes this substrate unable to take advantage of the ability of IP6 to crosslink with collagen, which is one of the key factors in improving bonding to dentin. Though an ideal etch pattern is not essential to produce high bond strength to enamel [36,37], excessive etching whether by increasing the concentration or the application of time of the etchant would result in compromised bonding to enamel as a result of decreased hardness of this substrate [38,39]. IP6 is a stronger acid compared to phosphoric acid and has six phosphate groups with two dissociable OH groups in each phosphate [39].…”
Section: Discussionmentioning
confidence: 99%
“…At high levels, however, uoride affects the development of teeth and bone. Speci cally, DF is caused by the ingestion of excess uoride mainly through the drinking of water [17,18]. Additionally, the use of uoride is related to the exacerbation of DF.…”
Section: Discussionmentioning
confidence: 99%